INVESTIGATING ENERGY TRANSMISSION AND PERFORMANCE IN SEALED DIFFERENTIAL PLANETARY GEAR SYSTEMS: A DETAILED ASSESSMENT - Thompson, Adrian (Ayden International Journal of Basic and Applied Sciences, 2024)
Gears are integral to the manufacturing industry, and their significance spans across various sectors. A comprehensive investigation into gears is paramount for propelling China into the league of manufacturing powerhouses. Among the primary forms of mechanical transmission, gear transmission holds a pervasive presence in automobiles, ships, mining machinery, and more. In this realm, planetary gears, an amalgamation of traditional gears, offer distinct advantages including compactness, enhanced power transmission, and robust load-bearing capabilities. One standout application is the closed differential planetary gear system, which combines the single degree of freedom star gear train (in the closed stage) with the closed two-degree freedom differential planetary gear train (in the differential stage). This configuration forms a closed differential planetary transmission system, leveraging multiple planetary gears (star wheels) to distribute the load and create a power diversion. This approach delivers compactness, reduced weight, and exceptional loadbearing capacity. In the context of advancing manufacturing prowess, understanding and optimizing this innovative transmission system is of paramount importance.